Screening for Adrenocortical and Thyroid Peroxidase Antibodies to Look for Underlying Autoimmune Etiologies in Women under 35 with Idiopathic Dimished Ovarian Reserve - Ipek Evruke; Ozlem Dural; Cemil Akgul; Cenk Yasa; Funda Gungor Ugurlucan; Cansu Evruke (Clinical and Experimental Obstetrics & Gynecology)
Background: Autoimmune disorders are more common in premature ovarian insufficiency (POI) than in the general population. The most important association is with autoimmune Addison’s disease. Measurement of adrenocortical antibodies (ACA) and/or 21-hydroxylase antibodies (21-OH) is recommended in every POI patients as they appear to be the marker with the highest diagnostic sensitivity for autoimmune POI. Also thyroid peroxidase autoantibodies (TPO-Ab) should be assayed due to the common association between thyroid disease and POI. The underlying etiologies of diminished ovarian reserve (DOR) in young women can be expected to be similar to the etiology of POI since they represent a continuum in the phenotypic expression of premature ovarian aging. Methods: This pilot case-control study was conducted between January 2019 and April 2020. The study group consisted of patients under the age of 35, who was infertile and diagnosed with idiopathic DOR by ovarian reserve tests during infertility work up. Controls were patients of the same age range who diagnosed with isolated tubal factor or male infertility and had functional ovarian reserve test results during infertility work up. Patients with a history of ovarian surgery, cancer, genetic or autoimmune disease were excluded. Abnormal ovarian reserve tests are defined as antral follicle count <5 and anti-mullerian hormone (AMH) <1.2 ng/dL corresponding to group 3 according to POSEIDON criteria. In total, 35 DOR patients and 35 controls were included in the study. ACA and TPO-Ab screening were performed in serum samples using indirect immunofluorescence method. Demographics and family history of autoimmune diseases were also evaluated. Results: A higher rate of ACA positivity was detected in the DOR group (34.3%) compare to controls (17.1%), although it was not found to be statistically significant (p = 0.101, p < 0.05). The incidence of family history of autoimmune diseases in first degree relatives was positively correlated with ACA positivity (p = 0.006, p < 0.05). In DOR group, autoimmune disease history in the family was significantly higher in ACA (+) patients compared to ACA (–) individuals (p = 0.03, p < 0.05). TPO-Ab positivity rates were similar between 2 groups (17.1% vs 20%, p = 0.759, p < 0.05). Conclusions: Even if there is no specific treatment option yet for autoimmune ovarian damage, screening for ACA or 21-OH antibodies may be considered in young women with idiopathic DOR, especially those with a family history of autoimmune disease, based on knowledge that identification of women with autoimmune POI is clinically important for the identification of subclinical autoimmune Addison’s cases.